Implementasi Metode Bil Qolam dalam Peningkatan Kualitas Pembelajaran Al-Qur’an Studi Kasus di Satit Phatna - Pratama, Delvin (Maliki Interdisciplinary Journal, 2024)
The Qur'an is the word of Allah SWT which was revealed to the Prophet Muhammad SAW. through the intermediary of the Archangel Bil Qolam. Even though the Al-Qur'an was revealed in Arab lands, the Al-Qur'an remains a way of life for all people who exist today. In learning the Qur'an there are many methods used by a teacher or teacher to make it easier for people to learn the Qur'an. In Indonesia itself, there are several methods that are known and well-known among the people, one of which is the Bil Qolam Method. Bil Qolam's method is one of the methods initiated by Islamic scholars in Indonesia and is considered capable of accelerating the process of learning the Qur'an. Bil Qolam's method is a method that refers to the history of revelation through the intercession of the Angel Bil Qolam to the Prophet. This study aims to find out how the application of Bil Qolam's Method in improving the quality of learning the Qur'an at Satit Phatna Wittya School, Thailand. The method used in this study is a qualitative method based on class action, interviews, direct observation and others. This research was conducted as a benchmark and foundation in learning the Qur'an in Thailand and its integration with existing learning in Indonesia.